Understanding the risks in work-integrated learning - Fleming J; Hay K (New Zealand Association for Cooperative Education)
Work-integrated learning (WIL) is an activity with inherent risks, different from those that occur with on-campus learning experiences. Risks associated with WIL may have serious financial, reputational and legal consequences for universities, WIL staff, students and host organizations. Using a mixed methods approach, this study examined how risk was defined and perceived by those involved in WIL, across eight New Zealand universities. Differences in understanding were examined and compared across disciplines and university roles. WIL staff perceived health and safety; conduct of students; student characteristics; conduct of the host organization (including exploitation and physical safety of students) as high risk. These factors were all linked to reputational risk for the university. WIL staff (both new and more experienced) need to have a clear understanding of the risks, so they can design risk management practices to help mitigate these risks for universities, students, host organizations, as well as themselves.